Environmental Health Study of Coastal Communities to Domestic Wastewater Risks in Medan City - Syaputri, Deli; Auliani, Restu; Rusli, Mustar; Sinaga, Jernita; Manik, Erba Kalo (West Science Nature and Technology, 2025)
This study examines the environmental health risks posed by domestic waste in coastal communities in Medan City, employing a quantitative approach with a sample of 150 respondents analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings highlight significant positive relationships between waste management practices, community awareness, and environmental health outcomes. Infrastructure adequacy further enhances the impact of waste management on health outcomes, demonstrating its moderating role. These results underscore the necessity of integrated strategies combining effective waste management, educational initiatives, and infrastructural investments to improve environmental health in coastal areas. This research provides actionable insights for policymakers and stakeholders, emphasizing the importance of sustainable waste practices to mitigate environmental and health risks.